The Effect of Student-Centered Learning with the Make a Match Method on Nursing Students’ Knowledge of Patient Safety Goals - Yunita Fitri Rejeki; Deris Riandi Setiawan; Adinda Triani Nur Hasanah (Karya Kesehatan Siwalima, 2025)
Understanding nursing students’ knowledge of the six patient safety goals is essential to prevent adverse events. Innovative and interactive learning strategies are needed to strengthen students’ comprehension of these goals. The make-a-match method, as a cooperative learning approach, encourages active engagement and is expected to enhance knowledge retention. This study aimed to examine the effect of patient safety goals education on the knowledge of undergraduate nursing students using the make-a-match method. A pre-experimental one-group pretest–posttest design was conducted with 69 undergraduate nursing students selected through purposive sampling. Data were collected using a structured patient safety goals knowledge questionnaire. The Wilcoxon signed-rank test was applied to analyze the differences between pretest and posttest scores, with a significance level of 0.05. Prior to the intervention, most participants demonstrated a moderate level of knowledge (63.8%). Following the intervention, the majority of students achieved a good level of knowledge (91.3%). Statistical analysis using the Wilcoxon test revealed a significant improvement in knowledge scores (p = 0.001, p < 0.05). The findings indicate that education using the make-a-match method is effective in improving nursing students’ knowledge of patient safety goals. This method may serve as a valuable learning strategy in nursing education to strengthen patient safety competencies.